2021
DOI: 10.1177/00368504211026162
|View full text |Cite
|
Sign up to set email alerts
|

Multi-element determination of essential and toxic metals in green and roasted coffee beans: A comparative study among different origins using ICP-MS

Abstract: The aim of this study is to compare the elemental composition among different coffee varieties consumed in Jordan. Levels of different metallic elements in coffee samples; green and roasted coffee beans from five origins; Brazil, Ethiopia, Kenya, Columbia, and India, collected from the Jordanian market were investigated. Twenty-two elements, including essential and toxic elements such as potassium (K), magnesium (Mg), calcium (Ca), iron (Fe), aluminum (Al), manganese (Mn), copper (Cu), barium (Ba), strontium (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 37 publications
1
20
1
Order By: Relevance
“…Based on the results from the study by Albals, et al [ 7 ] which investigated the heavy metals contents for the same coffee samples that were analyzed in this study, the data showed that there was no clear correlation between the content of phenols, antioxidant compounds, and heavy metals content. Therefore, these findings suggest that roasting degree would affect the antioxidant activity, regardless of the geographical origin or heavy metal content.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Based on the results from the study by Albals, et al [ 7 ] which investigated the heavy metals contents for the same coffee samples that were analyzed in this study, the data showed that there was no clear correlation between the content of phenols, antioxidant compounds, and heavy metals content. Therefore, these findings suggest that roasting degree would affect the antioxidant activity, regardless of the geographical origin or heavy metal content.…”
Section: Discussionmentioning
confidence: 79%
“…Figure 3 and Figure 4 show a comparison of coffee samples of different geographical origins (regardless of their roasting degree) and roasting degrees (regardless of their origin) in terms of average GAE in mg/g, average TEAC in mg/g, and average Zn, Pb, and Cu contents in µg/g (Data for heavy metal content was taken from Albals et al [ 7 ]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations